Electric car charging station location problem - Leng, Sebastian Tze Rong. (2013)
Accessing to the electric vehicle (EV) charging stations affects the users’ experience and adaptability of converting from a conventional in-combustion engine (ICE) vehicle to EV. With Singapore in the testing phase on the feasibility of EV, the study helps determine the optimised locations of the charging stations. Using data of past research on the statistics of a town in Singapore, the demand perimeters are predicted. Existing car parks are selected as potential sites for charging stations. Several of these variables are key inputs for a Mixed-integer Programming (MIP) model, used in this study for optimal EV charging station location assignment. The algorithm minimises the walking distance between the destinations to charging stations. The number of charging points needed at every assigned charging station is optimised, so as to improve the users’ adaptability and reduce the cost of building the charging points at the same time. The model developed is generalisable to different data sets of different towns in Singapore, and may be applied to other cities in the world, which helps the charging service provider companies and governments make more informed decisions on the positioning of the charging station.